DRAMA PERAMPASAN YANG DIBAYANGKAN: ARTIKULASI IDENTITAS DAN KEPEMILIKAN PRIMORDIAL KELOMPOK IDENTITAS ASLI PASCA ORDE BARU - Geger Riyanto (Masyarakat Indonesia, 2017)
The post-New Order period witnessed the resurgence of the discourse of indigenous identity in various lines of social life in Indonesia. As authenticity often underlies the claims, struggles, or protection of resource ownership in the diverse groups, the notion that the discourse of identity is recreated and manipulated in order to emphasize control over resources becomes commonplace. However, this article would like to show that moral intuition and supposition also have a meaningful contribution in enablingindigenous identity maneuvers. Regardless of the chance of securing resources, undeniably encouraged the parties to identify themselves as indigenous, the narratives of indigenous people’s rights are usurped by outsiders that constantly accompanying the rhetoric of the original identity group. By personalizing and simplifying impersonal entities such as corporations, states, immigrants become fictional human beings who violate their moral obligations by depriving what the original group actually possesses. As imagined as fictional human beings, primordial possession narrative has an evocative power that unifies members and invitee’s response of other parties. Furthermore, it also serves as a foothold of structures that bind and organize the actions of the human beings that involved. The rules, institutions, and maneuversof actors must be realized to comply with their discursive logic.Keywords: primordial ownership, identity recreated, indigenous identity, morality, reciprocal ABSTRAKPeriode pasca-Orde Baru menjadi saksi kebangkitan wacana identitas asli di berbagai lini kehidupan sosial di Indonesia. Seiring keaslian acap mendasari klaim, perjuangan, atau perlindungankepemilikan sumber daya pusparagam kelompok, gagasan bahwa wacana identitas direkacipta dan dimanipulasi demi menandaskan kontrol atas sumber daya menjadi lazim kita jumpai. Namun, artikelini hendak memperlihatkan, intuisi moral dan pengumpamaan juga mempunyai andil yang berarti dalam memungkinkan manuver-manuver identitas asli. Terlepas kesempatan-kesempatan mengamankan sumber daya tak bisa ditampik mendorong pihak-pihak untuk mengidentifikasi diri sebagai orang asli, narasi hak orang asli dirampas oleh orang luar senantiasa mengiringi retorika-retorika kelompok identitas asli. Dengan mempersonifikasi sekaligus menyederhanakan entitas impersonal seperti perusahaan, negara, pendatang menjadi insan khayali yang melanggar obligasi moralnya dengan merampas apa yang sejatinyadimiliki kelompok asli, yang sama-sama dibayangkan sebagai insan khayali, narasi kepemilikan primordial memiliki kekuatan menggugah, menyatukan para anggota maupun mengundang respons pihak-pihak lain. Lebih jauh, hal ini juga menjadi pijakan struktur yang mengikat dan menata tindakan-tindakan para insan yang terlibat di dalamnya. Aturan, lembaga, maupun manuver para aktor harus direalisasikan mematuhi logika diskursifnya.Kata kunci: kepemilikan primordial, rekacipta identitas, identitas asli, moralitas, timbal-balik